Relationship between Nurse Motivation and Workload with Completeness of Nursing Care Documentation - Tuti Sulastri; Hilda; Arsyawina (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
There are various factors that cause incomplete documentation of nursing care, including the motivation and workload of nurses. This study aims to determine the relationship between motivation and workload of nurses with the completeness of nursing care documentation in the inpatient room of RSUD Dr. Abdul Rivai Berau District. This research is quantitative with a cross sectional approach. the number of samples is 40 people, the sampling technique is total sampling. The instrument used was a Likert scale questionnaire. Data analysis techniques Univariate analysis with frequency distribution and bivariate analysis using the Fisher's exact test. The results of the analysis found that motivation with the completeness of nursing care documentation had a p value = 0.394 (p => 0.05), and the workload of nurses with the completeness of nursing care documentation p value = 1.000 (p = > 0.05) . So it can be concluded that there is no relationship between motivation and workload of nurses with the completeness of nursing care documentation in the internal room of RSUD Dr. Abdul Rivai Berau District. It is expected that nurses can maintain the completeness of their nursing care documentation.